2021
DOI: 10.1590/2317-6369000038218
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao sofrimento psíquico de agentes penitenciários do estado do Rio de Janeiro, Brasil

Abstract: Resumo Objetivos: analisar o sofrimento psíquico de agentes penitenciários do estado do Rio de Janeiro e apontar os fatores a ele associados no âmbito social, destacando o ambiente de trabalho. Métodos: estudo quantitativo e qualitativo. As unidades prisionais foram selecionadas por meio da amostragem estratificada. Utilizou-se a escala de sofrimento psíquico Self-Reported Questionnaire (SRQ20) e uma escala de apoio social. Variáveis explicativas foram relacionadas tanto ao perfil profissional como aos fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 18 publications
2
2
0
12
Order By: Relevance
“…Overcrowding proved to be the third most registered cause, followed by the high risk of detainees and the lack of communication between the levels of the Unit, which characterizes the five most relevant stressors. Such results are in agreement with the findings made by Bezerra et al (2021).…”
Section: Occupational Stressors and Coping Strategiessupporting
confidence: 94%
“…Overcrowding proved to be the third most registered cause, followed by the high risk of detainees and the lack of communication between the levels of the Unit, which characterizes the five most relevant stressors. Such results are in agreement with the findings made by Bezerra et al (2021).…”
Section: Occupational Stressors and Coping Strategiessupporting
confidence: 94%
“…Antunes 37 , in a literature review on that topic concluded that hierarchy defines work organization of military police and is considered a factor that contributes to suffering and health issues. The high frequency of non-psychotic symptoms found in this article, such as insomnia, irritability, headache and gastritis may be manifestations or answers to a type of psychological distress as described by Bezerra et al 9 . The recurrent narratives by interviewees who state that the problematical functioning of the institution's hierarchy is one of the worst aspects of being a police officer highlight the fact that the institution's work organization is a risk factor for the psychological suffering of injured police officers.…”
Section: Discussionsupporting
confidence: 57%
“…Studies have emphasized that these impacts on the health of police officers result from insalubrious working conditions, such as poor nutrition, work overload, a constant environment of violence that includes armed clashes and cause a high rate of victims. Work organization often clashes with the relations of police officers with their peers and superiors, they live in constant fear for their safety and society hardly recognizes police work 7,9 . Consequences of this working method also interfere with the mental health of their relatives 10 and impact their social relationships 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Antunes 37 , em revisão de literatura sobre o tema, concluiu que a hierarquia fundamenta a organização do trabalho das polícias militares e é considerada um fator colaborador na emergência de sofrimento e implicações na saúde. A alta frequência de sintomas não psicóticos encontrados neste artigo como insônia, irritabilidade, dor de cabeça e gastrite podem ser manifestações ou respostas a um tipo de sofrimento psicológico como descrito por Bezerra et al 9 . As recorrentes narrativas entre os entrevistados atribuindo o funcionamento problemático na hierarquia da instituição ao pior de ser policial apontaram para essa realidade de a organização do trabalho da instituição como fator de risco para o sofrimento psíquico dos policiais feridos.…”
Section: Discussionunclassified
“…Trabalhar não se resume a produzir, mas é transformar a si mesmo. Estudos têm apontado que estes impactos na saúde dos policiais decorrem de condições insalubres de trabalho com alimentação precária, sobrecarga de trabalho, ambiente constante de violência com confrontos armados produzindo alta taxa de vitimização, uma organização do trabalho muitas vezes conflitante nas relações dos policiais com seus pares e superiores hierárquicos, baixo reconhecimento da sociedade pelo trabalho policial e o medo constante quanto a segurança de sua vida 7,9 . As consequências desta forma de trabalho têm interferido também na saúde mental de seus familiares 10 com desdobramentos em suas relações sociais 11 .…”
Section: Introductionunclassified